2020
DOI: 10.3389/fgwh.2020.00001
|View full text |Cite
|
Sign up to set email alerts
|

Moms Are Not OK: COVID-19 and Maternal Mental Health

Abstract: Introduction: Depression and anxiety affect one in seven women during the perinatal period, and are associated with increased risk of preterm delivery, reduced mother-infant bonding, and delays in cognitive/emotional development of the infant. With this survey we aimed to rapidly assess the influence of the COVID-19 pandemic and subsequent physical distancing/isolation measures on the mental health and physical activity of pregnant and postpartum women.Methods: Between April 14 and May 8, 2020, we recruited wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

55
538
15
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 499 publications
(623 citation statements)
references
References 23 publications
55
538
15
15
Order By: Relevance
“…The present study ndings show that the prevalence of postpartum depressive and post-traumatic stress symptoms among the women experiencing childbirth during the Covid-19 pandemic was higher than that reported in previous studies before the pandemic. Literature data report that approximately 10-16% of women met major depression's criteria at 3 months postpartum [24,[33][34][35][36]. The ndings for our cohort (30.7%) are shared by a recent study that reported that 30% of the mothers who delivered during the Covid-19 pandemic had a global EPDS score > 12 compared with 11.9% in an antecedent matched group of postpartum women [36].…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The present study ndings show that the prevalence of postpartum depressive and post-traumatic stress symptoms among the women experiencing childbirth during the Covid-19 pandemic was higher than that reported in previous studies before the pandemic. Literature data report that approximately 10-16% of women met major depression's criteria at 3 months postpartum [24,[33][34][35][36]. The ndings for our cohort (30.7%) are shared by a recent study that reported that 30% of the mothers who delivered during the Covid-19 pandemic had a global EPDS score > 12 compared with 11.9% in an antecedent matched group of postpartum women [36].…”
Section: Discussionsupporting
confidence: 51%
“…The ndings for our cohort (30.7%) are shared by a recent study that reported that 30% of the mothers who delivered during the Covid-19 pandemic had a global EPDS score > 12 compared with 11.9% in an antecedent matched group of postpartum women [36]. An EPDS score > 13 was self-identi ed by another online survey in 15% of women before and in 40.7% during the outbreak for the same cohort of women who were pregnant or within the rst year after delivery [35].…”
Section: Discussionmentioning
confidence: 97%
“…Importantly, the distinction between our method of universally screening all postpartum patients and previous studies exploring maternal mood during the COVID-19 pandemic (25-28) likely explains, at least in part, the differences in our ndings compared to theirs. That is, they not only did not differentiate between SES, but in addition likely suffered from well understood methodological limitations associated with sampling bias in choosing only to study individuals who independently responded to social media announcements (25,26), anonymously e-mailed online survey requests (27) or other voluntary participation requests (28). Second, we were unable to analyze the data for demographic differences beyond SES.…”
Section: Resultsmentioning
confidence: 99%
“…Reduced pollution levels, a decline in the rates of automobile accidents, and a lower incidence of non-COVID infectious disease (24) all appear secondary to imposed social, educational and employment restrictions. Unsurprisingly, early explorations into the impact of the COVID-19 pandemic on maternal populations have reported increases in anxiety and depression (25)(26)(27)(28). While these ndings represent valuable contributions to the literature, the majority of these studies have suffered from important methodological limitations, including relying solely on self-selection recruitment methods, such as social media advertisements (25,26) and e-mailed online surveys (27) that are prone to biased sampling, may directly in uence outcome measures, and are well understood threats to the generalizability of the ndings.…”
Section: Introductionmentioning
confidence: 99%
“…Higher scores indicate greater anxiety. A score >=40 is considered indicative of clinically signi cant anxiety symptoms [13].…”
Section: Instrumentmentioning
confidence: 99%